EFEKTIFITAS DAN KONTRIBUSI RETRIBUSI DAERAH TERHADAP PENINGKATAN PENDAPATAN ASLI DAERAH KABUPATEN SAMBAS - Muhammad Wawan Gunawan; Muhammad Adib Alfarisi; Rettie Angrayni (Politeknik Bisnis Indonesia, 2023)
Regional levies are one of the contributors to Regional Original Revenue (PAD) in Sambas Regency. However, the effectiveness and contribution of regional levies to PAD is still felt to be not optimal, and it has not reached the targets set for the 2017-2021 period. The purpose of this study was to find out (1) The effectiveness of regional fees for Sambas Regency in 2017-2021 (2) The contribution of regional fees to increasing PAD for Sambas Regency in 2017-2021. This study uses a descriptive method with a quantitative approach. The data used is secondary data in the form of target data and realization of regional retribution and PAD, obtained from the Regional Medium Term Development Plan (RPJMD) and Regional Government Financial Statements (LKPD) of Sambas Regency. The conclusions from this study are (1) In 2018, 2020 and 2021 the realization of regional levies in Sambas district is in the less effective category, whereas in 2017 and 2019, it is not effective because its effectiveness is below 60%. (2) The realization of the regional retribution contribution to Sambas Regency PAD in 2017-2021 is in the very under-contributing category because the achievement is below 10%, with an average of 2.33% over a period of five years. Regional levies are one of the contributors to Regional Original Revenue (PAD) in Sambas Regency. However, the effectiveness and contribution of regional levies to PAD is still felt to be not optimal, and it has not reached the targets set for the 2017-2021 period. The purpose of this study was to find out (1) The effectiveness of regional fees for Sambas Regency in 2017-2021 (2) The contribution of regional fees to increasing PAD for Sambas Regency in 2017-2021. This study uses a descriptive method with a quantitative approach. The data used is secondary data in the form of target data and realization of regional retribution and PAD, obtained from the Regional Medium Term Development Plan (RPJMD) and Regional Government Financial Statements (LKPD) of Sambas Regency. The conclusions from this study are (1) In 2018, 2020 and 2021 the realization of regional levies in Sambas district is in the less effective category, whereas in 2017 and 2019, it is not effective because its effectiveness is below 60%. (2) The realization of the regional retribution contribution to Sambas Regency PAD in 2017-2021 is in the very under-contributing category because the achievement is below 10%, with an average of 2.33% over a period of five years.